THE CORRELATION OF THE HIGH-RESOLUTION CT SCAN WITH THE OPERATIVE FINDINGS IN PATIENTS WITH CHRONIC OTITIS MEDIA UNDERGOING TYMPANOMASTOIDECTOMY: A DESCRIPTIVE STUDY - Baban, Muaid I. Aziz (Journal of Sulaimani Medical College, 2022)
Background The prior knowledge of the normal anatomy and disease extension in chronic suppurative otitis media (CSOM) is essential in the decision-making and planning of their surgical approach. Especially with the development of high-resolution computed tomography (HRCT), which provides good topographic viewing without the artefacts caused by the superimposition of structures. Objectives To point out the accuracy of the HRCT scan in correlation to intraoperative findings of CSOM diseases in predicting the disease’s extent and taking surgical decisions. Patients and Methods A Prospective study conducted at the Department of Otolaryngology-Head & Neck Surgery (Sulaimani Teaching Hospital, College of Medicine – the University of Sulaymaniyah, Kurdistan Region –Iraq. Patients who had CSOM and were listed for mastoid surgery were included in the study. All included patients underwent HRCT preoperatively, and each image was analyzed on Osirix software to define the anatomical structures. Evaluation of pathologies of the temporal bone was recorded in a radiology proforma. A similar proforma itemized the intraoperative findings, compared them to the radiological records, and statistically analyzed them using the statistical package for social sciences (SPSS, version 19). Results Thirty-five patients were included in this study, and their findings showed the significance of sensitivity and specificity of HRCT in comparison to surgical findings as follows; scutum erosion was 88.9%, 96.9%, ossicle erosion was 100%, 96%, and 68.4%, 100% for malleus and incus erosion respectively. Moreover, facial nerve canal erosion with a sensitivity of 28.6% and 92.9% specificity. Lateral semicircular canal (LSSC) erosion with a sensitivity of 50% and specificity of 93.9%. Tegmen, posterior canal wall, and sigmoid sinus wall integrity with a sensitivity and specificity of 66.7%/ 96.9%, 83.3%/89.7%, and 100%/ 96%, respectively. Conclusion High-resolution computed tomography scan is a valuable modality in the preoperative assessment of temporal bone pathologies in patients with chronic suppurative otitis media with reasonable accuracy and precision for taking surgical decisions.
Keywords: Chronic suppurative otitis media; High-resolution CT scan; Temporal bone; Tympano-mastoid surgery